The Link Between Everyday Discrimination, Healthcare Utilization, and Health Status Among a National Sample of Women - Fazeli Dehkordy, Soudabeh (J Womens Health (Larchmt), 2016)
Background: Research has not adequately examined the potential negative effects of perceiving routine discrimination on general healthcare utilization or health status, especially among reproductive-aged women. We sought to evaluate the association between everyday discrimination, health service use, and perceived health among a national sample of women in the United States. Materials and Methods: Data were drawn from the Women's Healthcare Experiences and Preferences survey, a randomly selected, national probability sample of 1078 U.S. women aged 18–55 years. We examined associations between everyday discrimination (via a standardized scale) on frequency of health service utilization and perceived general health status using chi-square and multivariable logistic regression modeling. Results: Compared with women who reported healthcare visits every 3 years or less (reference group), each one-point increase in discrimination score was associated with higher odds of having healthcare visits annually or more often (odds ratio [OR] = 1.36, confidence interval [95% CI] = 1.01–1.83). Additionally, each one-point increase in discrimination score was significantly associated with lower odds of having excellent/very good perceived health (OR = 0.65; 95% CI = 0.54–0.80). Conclusion: Perceived discrimination was associated with increased exposure to the healthcare setting among this national sample of women. Perceived discrimination was also inversely associated with excellent/very good perceived health status.